Analysis of Akure Urban Land Use Change Detection from Remote Imagery Perspective. (6th April 2016) - Owoeye, Julius Oluranti; Ibitoye, Oyewole Amos
Abstract : This study presents the analysis of Akure urban land use change detection from remote imagery perspective. Efforts were made to examine the direction that the continuous expansion of the city tends towards since its inception as a state capital in 1976. Using Aerial Imagery Overlay (AIO), the pattern of land use changes in Akure and its environs were determined. This involves imageries interpolation and overlaying to determine the land use changes, direction, and extent of the expansion. Findings revealed unguided expansion in the growth of the city which affects the pattern of land uses within the city and, by extension, into the adjoining settlements. There were incompatible conversions in land uses and undue encroachment into green areas in the adjoining communities. The study suggests effective zoning strategy on unguided nature of urban development whose effects on land use are very prominent in the study area. Adequate monitoring by the Development Control Department and other stakeholders in urban planning is equally suggested to mitigate the incompatible land use changes in the area.